EVALUATION OF THE SOCIOECONOMIC STATUS OF PATIENTS RECEIVED AT RADIOLOGY DEPARTMENT, HAYATABAD MEDICAL COMPLEX PESHAWAR - Wahid, Ghazala; Ahmad, Adnan; Tariq, Rabiya; Tamkeen, Naila; Samad, Mehreen; Khan, Mahnoor Rehman (Journal of Postgraduate Medical Institute, 2022)
Objectives: To determine the socio-economic status of patients availing Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) at the Radiology Department, Hayatabad Medical Complex. Methodology: This cross-sectional study was conducted in Hayatabad Medical Complex, Peshawar, between August 2018 and January 2019. The study group included 355 patients availing of CT and MRI facilities in the hospital. A systematic random sampling method was used to collect data. Data was collected through an open-ended questionnaire. The cost & type of the investigation was documented. Modified Kuppuswamy's Scale was used to collect the data and was analyzed appropriately. Results: The majority of the patients belonged to the lower-middle socio-economic class representing 38.87% of the study population. Second, the highest percentage of patients were from the upper lower stratum constituting 21.69%, while 19.44% were from upper-middle households whereas 11.83% were from lower socioeconomic classes. whereas, 8.17% belonged to the high socio-economic stratum. The average monthly household income in the lower-middle-class group was calculated to be approximately Rs. 15,000/-. 98% of patients used out-of-pocket methods for payment exposing them to the risk of increased expenditure. 5.92% of patients utilized the government-funded facility or ‘poor-free’ facility for free cost scan; or relied on donations from other sources. Conclusion: Most of the patients were restricted in terms of their financial resources with the largest percentage of patients belonging to lower-middle-class households. Low socioeconomic status was found to be associated with missed appointments & delays in availing the CT and MRI scans.